Analysis of Fatigue Management Implementation on ATC Performance at ACC Unit of AirNav Indonesia JATSC - Artias Widianingrum; Lina Rosmayanti; Yudha Abimanyu (CV. AFDIFAL MAJU BERKAH, 2026)
Air Traffic Controllers (ATCs) play a critical role in ensuring flight safety but are highly vulnerable to fatigue due to intensive workload demands. This study aims to analyze the implementation of the Fatigue Management System (FMS), identify contributing factors of fatigue, and evaluate the relationship between FMS, fatigue levels, and ATC performance at the Area Control Center (ACC) of AirNav Indonesia, Jakarta Air Traffic Service Centre (JATSC). A descriptive quantitative design with a cross-sectional approach was employed, involving 115 ATC respondents. Data were collected using a validated questionnaire and analyzed through descriptive statistics and Pearson correlation. The results revealed that FMS implementation was in the “Good” category (mean score 3.62), with strong aspects in rest facilities and shift scheduling but weaknesses in reporting and monitoring systems. Organizational factors showed the strongest negative correlation with fatigue (r = -0.451, p < 0.001). FMS was negatively correlated with fatigue (r = -0.407, p < 0.001) and positively correlated with performance (r = 0.306, p < 0.001). The findings confirm that effective fatigue management supports high ATC performance and operational safety, highlighting the need for improvements in fatigue reporting, psychological support, and staffing adequacy.